2021
DOI: 10.1186/s12913-021-06181-1
|View full text |Cite
|
Sign up to set email alerts
|

Embedding an economist in regional and rural health services to add value and reduce waste by improving local-level decision-making: protocol for the ‘embedded Economist’ program and evaluation

Abstract: Background Systematic approaches to the inclusion of economic evaluation in national healthcare decision-making are usual. It is less common for economic evaluation to be routinely undertaken at the ‘local-level’ (e.g. in a health service or hospital) despite the largest proportion of health care expenditure being determined at this service level and recognition by local health service decision makers of the need for capacity building in economic evaluation skills. This paper describes a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…This site was unique -the others being large health services centred on hospitals. The full planned program protocol, including a brief literature review and overview has been reported in an earlier edition of this journal [30]. The conceptual underpinnings are also reported elsewhere in detail [31].…”
Section: The Embedded Economist (Ee) Programmentioning
confidence: 99%
See 3 more Smart Citations
“…This site was unique -the others being large health services centred on hospitals. The full planned program protocol, including a brief literature review and overview has been reported in an earlier edition of this journal [30]. The conceptual underpinnings are also reported elsewhere in detail [31].…”
Section: The Embedded Economist (Ee) Programmentioning
confidence: 99%
“…3. To facilitate health service practice change and the routine application of economic evaluation principles in decision making [30].…”
Section: The Embedded Economist (Ee) Programmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Central among the key principles proposed for effective KM is fostering and sustaining relationships between researchers and research users over time (as interactions and collaboration co-produce knowledge). 4,6 Our own work on embedded economic research 7 suggests that strong relationships are integral to influence and learning and time is essential to building these. 5 The approaches reported by RTC Board members: participatory, capacity building, co-production and clinical engagement -are all relationship building.…”
Section: Knowledge Mobilisation -Do We Know Exactly What Should Be Done?mentioning
confidence: 99%